Professional Skepticism, Professional Ethics, and Ethical Sensitivity in the Detection of Auditor Fraud - Fidia Sanditha; Yusnaini Yusnaini (GLOBAL SCIENTS PUBLISHER, 2026)
his study aims to explore the role and interaction between professional skepticism, professional ethics, and ethical sensitivity in enhancing auditors' ability to detect fraud. Grounded in Agency Theory and Self-Determination Theory, this research highlights the importance of mitigating information asymmetry and fostering intrinsic motivation within audit practices. Using the Systematic Literature Review (SLR) method, 25 articles indexed in Q1, Q2, and SINTA from the 2021–2025 period were synthesized, concluding that professional skepticism, professional ethics, and ethical sensitivity are three interrelated pillars that play crucial roles in fraud detection. The findings confirm that professional skepticism serves as the operational foundation, the effectiveness of which is influenced by individual factors such as personality and ethical orientation, as well as situational factors including training, communication, and audit committee support. Professional ethics, particularly those grounded in idealism, shape skeptical character and guide auditors in responding appropriately to red flags, while ethical sensitivity acts as an early warning system enabling auditors to recognize ethical issues in complex audit situations. These findings provide practical implications for regulators and audit firms to shift focus from mere procedural compliance toward strengthening auditors’ internal capacity, developing ethical character, and sharpening ethical sensitivity through continuous training programs and building an organizational culture that supports skeptical and ethical behavior to maintain public trust.